Pengembangan E-Modul Berbantuan Canva Pada Materi Asmaul Husna - isnani, vara; Fitriyani Ishak; Sitti Marwiyah (South Sulawesi Education Development, 2024)
Abstract This research uses R&D (Research and Development) research. Researchers use the ADDIE development model with five development stages, namely analysis, design, development, implementation and evaluation. This research was conducted at MTs Satu Atap Datok Sulaiman Palopo. The subjects in this research were students in class VII A for the 2023 academic year. The data collection techniques in this research were validation sheets for media experts, validation sheets for material experts and student response questionnaire sheets. The data analysis techniques used are qualitative descriptive analysis and quantitative descriptive analysis. The results of this research show that: 1). steps in developing a product in the form of e-module learning media for learning aqidah and morals for class VII A using the ADDIE development model which consists of five stages: analysis, design, development, implementation and evaluation. 2) the researchers' efforts to determine the learning outcomes and learning interests of students in class VII A at MTS Satu Atap Datok Sulaiman Palopo, the students were very enthusiastic and this e-module was very helpful in the learning process because of its complete features. 3). The validity of e-module media in learning aqidah and morals in class VII A at MTs Satu Atap Datok Sulaiman Palopo by media experts obtained a percentage result of 77%, 90% by material experts, and 88% was obtained from student responses. So based on the results of the feasibility test, it was concluded that the E-Module media was very valid/very suitable for use.